EFFECT OF MASS AND HEAT TRANSFER IN OSCILLATORY TWO DIMENSIONAL FLOW OF A MICRO POLAR FLUID OVER AN INFINITE PERMEABLE PLATE IN A POROUS MEDIUM UNDER THE EXISTENCE OF MAGNETIC FIELD - Kumar, Ashok; Chawla, Jyoti (International Journal of Engineering Technologies and Management Research, 2018)
In this paper we study the effect of Mass and Heat transfer under the existence of transverse magnetic field for an oscillating two dimensional Micro-polar fluid flow through a moving infinite permeable plate in a porous medium. Investigate the Solutions for angular momentum, governing momentum, energy and concentration equations. Study the effect of chemical reaction, permeability parameters, velocity profiles, micro rotation profiles, wall stress coefficient and skin friction coefficient by using graph.